2017
DOI: 10.1007/s00344-017-9739-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Herbivore Stress- and Phytohormone-Mediated Urease Expression in Soybean (Glycine max)

Abstract: results show a significant increase of ubSBU transcripts upon jasmonic acid application and after herbivory, but downregulation after MecWorm treatment. UreG transcripts were downregulated after MecWorm, S. littoralis, and application of gibberellic acid, but upregulated by jasmonic acid. However, the ureolytic activities in leaves were influenced neither by phytohormones nor by herbivory and MecWorm. We conclude that the enzymatic activity of ureases is constitutive and basal levels of the enzyme are sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…New activation models suggested that nickel ion bound UreE enhances the GTP-uptake by binding with UreG in the presence of magnesium ion and nickel ion also translocated to the UreG and then an apo-urease complex formed Ni 2+ -(UreDFG) 2. GTP hydrolysis by UreG, specifically catalysed by KHCO 3 /NH 4 CO 3 results in the activation of the urease enzyme (Menegassi et al, 2018). The pathway showing the activation mechanism of urease is shown in Fig.…”
Section: Activation Mechanism and Complex Of Ureasementioning
confidence: 99%
“…New activation models suggested that nickel ion bound UreE enhances the GTP-uptake by binding with UreG in the presence of magnesium ion and nickel ion also translocated to the UreG and then an apo-urease complex formed Ni 2+ -(UreDFG) 2. GTP hydrolysis by UreG, specifically catalysed by KHCO 3 /NH 4 CO 3 results in the activation of the urease enzyme (Menegassi et al, 2018). The pathway showing the activation mechanism of urease is shown in Fig.…”
Section: Activation Mechanism and Complex Of Ureasementioning
confidence: 99%
“…A soja (Glycine Max) é uma leguminosa importante que contém cerca de 40% de proteína, 34% de carboidratos e 21% de óleo (MENEGASSI et al, 2018) sendo a cultura mais produzida no Brasil que, segundo a CONAB (2023) apresentou uma produção de 154,57 milhões de toneladas na safra 2021/22. Após a colheita dos grãos é imprescindível manter ou minimizar sua qualidade, destacando-se a importância das tecnologias para o armazenamento de grãos na etapa pós-colheita, devido a necessidade de manutenção da qualidade dos grãos durante todo o tempo em que são acondicionados, antes de serem transformadas em diversos subprodutos por meio da industrialização (CARVALHO; RODRIGUES, 2023).…”
Section: Introductionunclassified
“…Rechenmacher et al [14] has reported that there are three urease isoforms in soybean: the embryospecific encoded by the Eu1 gene, as well as the ubiquitous urease encoded by Eu4 and Eu5.Pure urease extracted from legumes can produce a kit for clinical diagnosis of urea ammonia in serum, regeneration of the dialysate solution in the wearable kidney machine [15].When urease and urea are present at the same time, it provides N nutrition of high concentration, which is continually beneficial to seed germination, plant development [14] and bioregenerative life support systems [16]. Moreover, ureases play a role in defense against insect and phytopathogenic fungi [17] .It was reported that it can increase the hydrolysis rate of urea up to 10 14 times [15]. However, in the field of agronomy, the hydrolysis rate of urea is related to the bioavailability of nitrogen [15].…”
Section: Introductionmentioning
confidence: 99%